Natural tree regeneration after selective cutting in a dry evergreen forest in Northeastern Thailand - DOKRAK MAROD; SARAWOOD SUNGKAEW; SATHID THINKAMPAENG; CHONGRAK WACHRINRAT; SUTHERA HERMHUK; KKAPHONG THONGSAWI; WONGSATORN PHUMPHUANG; ARERUT YARNVUDHI; CHATPIMUK YATAR; SOMBOON CHEYSAWAT; CHATCHAI SAWASMONGKOL (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Marod D, Sungkaew S, Thinkampaeng S, Wachrinrat C, Hermhuk S, Thongsawi J, Phumphuang W, Yarnvudhi A, Yatar C, Cheysawat S, Sawasmongkol C. 2024. Natural tree regeneration after selective cutting in a dry evergreen forest in Northeastern Thailand. Biodiversitas 25: 4074-4085. Forest degradation is a serious problem caused by anthropogenic disturbance, nevertheless, forest recovery rates vary among forest ecosystems. We investigated forest regeneration after selective cutting in a dry evergreen forest at the Wang Nam Khiao Forestry Research and Training Station (WFRS), Nakhon Ratchasima Province, Thailand. In 2002, a 1-ha permanent plot was established in the forest. All woody plant (sapling and trees) in the plot with Diameter at Breast Height (DBH) >2 cm were identified, and their DBHs and positions were recorded. Data on environmental and topographic factors and soil properties were collected to analyze their relationships with tree spatial distribution. Tree monitoring was conducted in 2004, 2018, and 2020 and forest dynamics were analyzed for the periods 2002-2004, 2004-2018, and 2018-2020. In 2020, we identified 3,669 trees of 91 species, 81 genera, and 36 families. Based on importance index values, the dominant tree species (all with DBH ?4.5 cm) were Walsura pinnata Hassk., Dialium cochinchinense Pierre, Hopea ferrea Laness., Hydnocarpus ilicifolius King and Vitex scabra Wall. ex Schauer. Based on the DBH class distribution, the natural regeneration of all woody plants tended toward a reverse J-shaped, indicating a good regeneration condition. The results of forest dynamics analysis showed that the net recruitment rate (2.75±1.70% year-1) was higher than the mortality rate (2.14±0.73% year-1) throughout the study period. Tree spatial distributions varied among species and across environmental factors which were strongly influenced by soil texture followed by topographic and can be divided into generalist and specialist species. This indicates that the forest is going toward a positive regeneration trajectory after the disturbances. Nonetheless, additional information based on forest monitoring is required. Additionally, an understanding of the relationships between species niches and environmental changes is important for tree regeneration research and forest restoration programs; it will allow better matching of tree species to their optimal environmental conditions, thereby increasing the likelihood of plant community success.